Identifying Higher-Order Thinking Skills on Lesson Plan: How Do Teachers Construct the Lesson Plan? - Haryati, Sri; Trisnowati, Eli; Siswanto, Siswanto; Al Firdaus, Moch. Malik (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2021)
In line with 21st-Century learning, the 2013 Curriculum highlights the development of critical thinking, problem analysis, problem-solving, decision making, and creating something new. Professional teachers need to facilitate students in developing these abilities. This research describes how the teachers plan the higher-order thinking skills (HOTs). This research is qualitative research with a descriptive design. The respondents were four teachers with 0-40 years of teaching experience. The data were collected qualitatively through documentation and interviews. The results showed that HOTs were not clearly expressed in the teacher's lesson plans at teaching experience levels of 0 to 10 years and 10 years to 20 years. Teachers with 20 to 30 years of teaching experience and 30 to 40 years of experience have expressed HOTs explicitly and completely in all parts of the lesson plan. Teachers have an important role in facilitating higher-order thinking skills that can be seen through the lesson plans. The lesson plan must describe the development of higher-order thinking skills holistically. Teachers need to review each lesson plan to be coherent in every part and relevant to 21st-century learning.